Analysis Of Factors Influencing The Number Of Poor Population Provincial Central Kalimantan - Mariduk Manurung; Misel Jaya (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2018)
ABSTRACT The purpose of this study is to analyze the factors that affect the number of poor people of Central Kalimantan Province. The data used in this study is secondary data obtained from the Central Bureau of Statistics (BPS) of Central Kalimantan Province. The research method used is Ordinary Least Square Method (OLS), multiple linear regression method and to manage the data using SPSS version 17 software. The results of this study indicate that: a) Economic growth has a positive and insignificant effect on the number of poor people of Central Kalimantan Province. b) Per capita income has a negative and significant effect on the number of poor people of Central Kalimantan Province c) Inflation has a positive and significant impact on the number of Poor People of Central Kalimantan Province. d) Open Unemployment has a positive and insignificant effect on the Number of Poor People of Central Kalimantan Province. as well as the variables of these studies together significantly affect the Poor Population of Central Kalimantan Province.